Comparative Analysis Of The Health Of Syariah And Conventional Commercial Banks In Indonesia Using The Rgec Method - Suprapto, Ribut; Susanti, Nawal Ika; Mamlukhah, Mamlukhah; Sa'adah, Irma (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2025)
The objectives of this study are analyzing financial ratios consisting of Non-Performing Financing (NPF) and Financing to Deposit Ratio (FDR, Good Corporate Governance (GCG) Return On Assets (ROA) and Capital Adequacy Ratio (CAR) can distinguish health between the Islamic banking group and the conventional banking group. This study uses a quantitative approach to the type of comparative research. The sample selection in this study used a non-probability sampling method which was purposive sampling with the following criteria: financial banking which has two sharia and conventional systems, financial banking which issued 10 consecutive financial statements, financial statement banking which had the highest assets in 2011- 2020, and banks whose financial statements whose profit and loss present data on outstanding shares and share prices. The results of the analysis of this study indicate that: 1) Financial ratios consisting of Non-Performing Financing (NPF) and Financing to Deposit Ratios (FDR, Good Corporate Governance (GCG) Return On Assets (ROA) and Capital Adequacy Ratio (CAR) are not have the ability to significantly distinguish between the Islamic banking group and the conventional banking group. The conclusion of the study shows that: 1) of the 4 (FOUR) financial ratios of Non-Performing Financing (NPF) and Financing to Deposit Ratios (FDR, Good Corporate Governance (GCG) Return On Assets (ROA) and Capital Adequacy Ratio (CAR), which analyzed, there is 1 (one) financial ratio that has the ability to distinguish significantly, namely the CAR ratio, because it has been proven by obtaining a significance value below 0.05, while the other 2 (two) financial ratios do not have the ability to distinguish (not a significant discriminator). between the Islamic banking group and conventional banking, including LDR and ROA, this is evidenced by the obtaining of a significance value above/greater than 0.05. 2) The soundness of conventional banking is better than the financial performance of Islamic banking.